An investigation of the sources and supply of coarse sediment input to a semi-arid channel reach - Frauenstein, Glenn Gavin (Rhodes University, Faculty of Science, Department of Geography, 1988)
This study comprises an investigation of the source and supply of coarse sediment input to a semi-arid channel reach. Despite a growing body of lIterature documentIng research of various aspects of sediment response in semi-arId areas, few studies attempt to integrate processes active in specific source areas wIth sediment supply to the channel. Detailed In the present study is an account of the processes active in the study area, identifIcation of source environments, a discussion of some of the factors affecting supply, a comparison of the effectiveness of gravItatIonal and fluvIal supply processes and an estImatIon of the time sequence of sediment supply to and removal from a channel reach. The above aspects of sediment supply are embodied In the aims set for the study. The study is conceptualIsed withIn the framework of a coarse sedIment supply model. The model is formulated from supporting literature and tested in the light of the results obtained through an investigation of the above aspects of sediment supply in the specIfic study area. The model is prImarily a qualitative one and the data collected intended to strengthen the qualitative nature of the model, while at the same time add at least some measure of quantification. Several reasons for studyIng coarse sediment behavIour in semI-arid areas are identIfied and include the need to improve the present lack of understanding of the relatIonship between supply and removal of sediment, the temporal dIstributIon of sediment discharge and the relatIve contrIbutions of coarse sediment to the overall load of rivers. The study area is located within the semi-arid Ecca basin north-east of Grahamstown. A specifIc channel reach is chosen withIn a sub-catchment (catchment B) of the Ecca catchment area as it has a variety of channel bank environments, is accessible through the entire reach, and the proximity of a raingauge and flow measurIng weir provide the necessary hydrometeorological inputs. The methods of observing sediment response from five data collection sites Include the use of slope or bank base sediment traps, erosion pins, tracer particle monitoring. sequential photographic surveys, and channel bed surface profile surveys. Hydrometeorological data is provided by records drawn from the data bank at the Hydrological Research Unit. Rhodes University. All rainfall records as well as channel flow data are available in the form of continuous records. Rainfall amount and intensity for any period could be extracted from these records. Data collection is confined to a period of two years, during which time the study area was visited on an approximate monthly basis. The index of erosivity (EIâ‚ƒâ‚€) could also be calculated from the hydrometeorological records and has been used as an integrated measure of rainfall intensity over the monthly period between site visits. The results are presented on a sample day for sample day basis. The sediment response data together with hydrological data is represented graphically for each sample day, of which there were nineteen. Discussion and interpretation of the results is left to a separate chapter. The interpretation of the results are based largely upon graphical representation of data time series and of interrelationships between some of the variables measured. The limited number of sample days together with the assumed auto correlation present in much of the data precluded the use of simple statistical testing procedures. The use of more complex procedures is not considered worthwhile and is unlikely to add to the interpretation of the results. Bedrock weathering is found to be a fairly active producer of coarse sediment on exposed shale bedrock outcrops through which sections of the channel are cut. The transport of the weathered detritus to the channel is attributed to a combination of gravitational and fluvial transport processes, with each process dominating at different times, depending on the magnitude of the climatic input. A tentative comparison of the effectiveness of the two processes reveals that both are capable of transporting similar amounts of sediment but on different time scales. The trends of sediment supply from the various bank environments display remarkable similarity , suggesting a measure of consistency of response to climatic input through the entire reach. Source areas of coarse sediment identified were limited to a small percentage of the total valley area and consisted almost entirely of the immediate channel environment. A tributary gully appears to be an important source of coarse sediment during fluvially dominated supply episodes, while the channel banks supply sediment on a quasi-continuous basis. The total yields for each source environment were extrapolated from the sampled amounts, revealing that channel banks are the predominant source environments. An attempt is made to assess the role of various factors which might affect sediment supply. The factors include rainfall amount and intensity, channel flow, geology/lithology, dip of strata, aspect of channel banks and size of weathered material. The findings, though not conclusive, do give some indication of the role of the above factors. It is suggested though that this particular aspect of sediment supply receive further attention in future research. Discussion on the time sequence of supply to and removal from the channel draws attention to a pulse- like movement of sediment 'waves' through the channel, and two scales of removal-accumulation cycles are identified. Finally the validity of the model is assessed and with the exception of a tributary inflow process not envisaged in the original model, is found to be an accurate representation of sediment supply in semi-arid areas, in both its static and dynamic phases. The suggestion is offered that future research on the sediment supply system, in all climatic regimes, can be conceptualised within the context of the basic model proposed in the present study. Specific components of the model should be quantified by numerous individual research efforts, and in this way, serve to build up the model into a widely applicable tool with which to interpret sediment supply
Keywords: Sedimentation and deposition -- Arid regions